Predictors of Cholesterol Lowering with Corn Oil Consumption: Results from a Pooled Analysis of Randomized, Free-living Feeding Trials (P08-112-19). (24th October 2019) - Maki, Kevin; Dicklin, Mary; Cassens, Martha; Bell, Marjorie; Bunczek, Michael; Eren, Fulya
Abstract: Objectives: This pooled analysis of data from two clinical trials was designed to evaluate potential predictors of lipid responses to corn oil consumption. Methods: Free-living subjects in two clinical feeding trials consumed study products made with corn oil (each 4 tablespoons per day) as part of their habitual diets for four weeks. Subjects were required to have fasting low-density lipoprotein (LDL-C) levels ≥115 and < 190 mg/dL and triglycerides (TG) < 375 mg/dL. Baseline, end of treatment and % changes from baseline in fasting LDL-C and non-high-density lipoprotein cholesterol (non-HDL-C) levels were analyzed in the per protocol samples for all subjects and according to the following subgroups: tertile of baseline LDL-C (< 122.5, 122.5–135.25 or > 135.25 mg/dL), median baseline saturated fatty acid intake (< or ≥ 11.9% of energy), median body mass index (BMI; < or ≥ 21.35 kg/m2), median age (< or ≥ 51 y), male or female and non-Hispanic white or other race/ethnicity. Within group p-values were generated using paired t-tests or, when the values were non-normally distributed, the Wilcoxon test. Results: Overall ( n = 42 subjects) median baseline LDL-C, non-HDL-C, total-C, HDL-C and TG concentrations were 139, 158, 208, 47 and 101 mg/dL, respectively, and the total-C: HDL-C ratio was 4.3. Changes from baseline in LDL-C and non-HDL-C levels during corn oil consumption in the overall sample were −4.3% and −3.5%, respectively. LDL-C and non-HDL-C responses were statistically significant for subjects in the highest baseline LDL-C tertile (−8.3%, P = 0.017 and −5.5%, P = 0.025, respectively) and for subjects with BMI below the median (−5.6%, P = 0.013 and −4.5%, P = 0.009, respectively). LDL-C and non-HDL-C responses did not reach statistical significance in any other subgroup. Conclusions: Higher baseline LDL-C and lower BMI were predictive of larger reductions in LDL-C and non-HDL-C, two major risk factors for cardiovascular disease, during corn oil consumption in a pooled analysis from two feeding studies. Funding Sources: ACH Food Companies, Inc.